Removal of ferum ions from acid mine drainage wastewater using jar test technique: Factorial design analysis - N A, Mohamad Basir; A A, Mohd Azoddein; A H, Abdul Razik; N A, A Azman (IOP Publishing Ltd, 2020)
A factorial experimental design technique was used to investigate the removal of “Fe2+” from wastewater Acid Mine Drainage (AMD) through jar adsorption test technique. Jar testing is expected to contribute to cost savings in chemicals from which ferum ion can also be extracted. The best condition for slag adsorption from AMD wastewater was obtained via a complete 16 factorial design experiment. Factorial design for screening is chosen to test four effects factors Basic Oxygen Furnace (BOF) slag dosage (0.2 and 2.0g), stirration speed (150 and 250 rpm), interval time (5 and 100 minute) and concentration (200 and 1000 ppm) at two levels. Metal removal capability was evaluated using adsorption result. Using statistical methods, the main effects and interaction effects of the four variables were analysed. A regression model was suggested, and the experimental data was found to match very well. The findings were statistically analyzed using the Student’s t-test, variance analysis, F-test and lack of fit to identify three most significant process variables that influence “Fe2+” removal percentage. Therefore concentration was found to be the most important variable in this analysis.